PERSEPSI PESERTA DIDIK TENTANG FUNGSI TES INTELEGENSI DI SMA 11 NEGERI PADANG - SATRIA, DAFIT; Kasih, Fitria; Nofrita, Nofrita (Bimbingan dan Konseling, 2014)
Â Beckground of this research is opinion of students about the function of intelligence test still not yet suitable with wish or aim, limitation of this research are : (1) studentâs perception about the function of intelligence test viewed from prediction, (2) ) studentâs perception about the function of intelligence test viewed from diagnose, (3) studentâs perception about the function of intelligence test viewed from evaluasi. The purpose of this research is to find out studentâs perception function of intelligence test. This research is descriptive quantitative. The subject or population of this study were 287 student, meanwhile sample of this study were 57 students. Selecting of sample was through simple random sampling technique.Â The data was compiled by questionnaires for students, while analysis data have done through percentage technique , The result of this research shows: (1)Â studentâs perception about the function of intelligence test at senior high eleven padang viewed from prediction about competenceâs level and successâs level of students state at enough good category with percentage 54,38 %, (2) studentâs perception about the function of intelligence test at senior high eleven padang viewed from diagnose about formulation of the problemÂ and speculation that give effect for Â students state at enough good category with percentage 52,63 %, (3) studentâs perception about the function of intelligence test at senior high eleven padang viewed from evaluasi about self comprehension, self evaluation and self acceptance of students state at category enough good with percentage 59,64 %.